2010
DOI: 10.1590/s1413-81232010000400030
|View full text |Cite
|
Sign up to set email alerts
|

O impacto das condições bucais na qualidade de vida de pessoas com cinquenta ou mais anos de vida

Abstract: O impacto das condições bucais na qualidade de vida de pessoas com cinquenta ou mais anos de vidaThe impact on life quality due to oral conditions in people fifty years or above

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
21
0
9

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 5 publications
2
21
0
9
Order By: Relevance
“…This association may be explained by the fact that dental caries can cause pain, functional limitation, concern, or disappointment in relation to one's mouth or teeth, thereby jeopardizing physical, social, and psychological aspects of adolescents' lives. Previous studies also identified an association between need for dental treatment and severity of impact 35,36 .…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…This association may be explained by the fact that dental caries can cause pain, functional limitation, concern, or disappointment in relation to one's mouth or teeth, thereby jeopardizing physical, social, and psychological aspects of adolescents' lives. Previous studies also identified an association between need for dental treatment and severity of impact 35,36 .…”
Section: Discussionmentioning
confidence: 83%
“…The low figures for this variable may have contributed to the low perception of impact. Studies in adults reported a positive association between tooth loss and severity of impact 36 , and one study in adolescents also found this association 35 . The lack of association between DAI and severity of impact may be explained by the fact that OHIP-14 was not developed specifically to measure the impact of dental problems, and most of its items are not necessarily relevant to individuals with malocclusion.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…While the dentist evaluates the condition based on the presence or absence of disease, the patient gives more importance to symptoms and functional and social problems that may be triggered by the presence of the disease 17 . In this context, it is observed in the literature that some studies have shown differences between clinical conditions and patient self-perception 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Bianco et al 14 , em seu estudo sobre impacto das condições bucais na qualidade de vida, traz conceitos em relação a diversos itens ou domínios associados a melhora ou piora nas atividades cotidianas. Questionamentos em relação à dor, limitação funcional, desconforto psicológico, incapacidade física, social e psicológica relacionadas às condições bucais devem ser realizados para que a completa contemporização da qualidade de vida do paciente seja realizada.…”
unclassified